The 'Southernisation' of development?. (15th July 2018) - Mawdsley, Emma
Abstract : A more polycentric global development landscape has emerged over the past decade or so, rupturing the formerly dominant North–South axis of power and knowledge. This can be traced through more diversified development norms, institutions, imaginaries and actors. This paper looks at one trend within this turbulent field: namely, the ways in which 'Northern' donors appear to be increasingly adopting some of the narratives and practices associated with 'Southern' development partners. This direction of travel stands in sharp contrast to expectations in the early new millennium that the (so‐called) 'traditional' donors would 'socialise' the 'rising powers' to become 'responsible donors'. After outlining important caveats about using such cardinal terms, the paper explores three aspects of this 'North' to 'South' movement. These are (i) the stronger and more explicit claim to 'win‐win' development ethics and outcomes; (ii) the (re)turn from 'poverty reduction' to 'economic growth' as the central analytic of development; and (iii) related to both, the explicit and deepening blurring and blending of development finances and agendas with trade and investment.